Students’ perceptions on teaching effectiveness among lecturers - Ismail, Normala; Khalid, Mohamad Kamil Ariff (UiTM Cawangan Johor, 2021)
The role lecturers in determining students' academic excellence is important. No matter how smart a student is, the knowledge gained may not be effective without a teaching of lecturer. The effectiveness of lecturers' teaching from the perceptive of students is important in producing an excellent student who is able to overcome various obstacle in life and become an asset to a country. Thus, the purpose of this study is to examine the students' perceptive of the effectiveness of lecturers' teaching Economic courses.